2018
DOI: 10.1007/s12630-018-1234-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of peripheral nerve blocks with postoperative outcomes in ambulatory shoulder surgery patients: a single-centre matched-cohort study

Abstract: Purpose Regional anesthesia may have immediate postoperative advantages compared with general anesthesia, but its impact on post-discharge outcomes is poorly described. Our objective was to measure the association between regional anesthesia and outcomes after ambulatory shoulder surgery. Methods We conducted a historical cohort study at The Ottawa Hospital. Adults C 18 yr old having elective ambulatory shoulder surgery from January 1, 2011 to December 31, 2016 were included. Using one-to-many coarsened exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Jensen et al 7 found that continuous peripheral nerve blocks are associated with increased rates of ED visits after arthroscopic rotator cuff repair (6.71% vs 4.74%, P < 0.02), and King et al 26 reported that unanticipated health care resource utilization related to continuous peripheral nerve blocks in upper extremity surgery may approach 38%. Hamilton et al, 27 however, did not find increased ED resource utilization among 2207 patients undergoing elective shoulder surgery with and without blocks at their institution, a finding corroborated by their subsequent population study of 59 644 Ontario residents. 4 Liu et al reported that among 103 476 patients undergoing outpatient arthroscopic surgery at 243 facilities in New York state, the most common reason for an unanticipated acute care encounter within 7 postoperative days (ie, inpatient or ED encounter) is musculoskeletal pain (23.8% of the 1867 acute care patient encounters).…”
Section: Discussionmentioning
confidence: 79%
“…Jensen et al 7 found that continuous peripheral nerve blocks are associated with increased rates of ED visits after arthroscopic rotator cuff repair (6.71% vs 4.74%, P < 0.02), and King et al 26 reported that unanticipated health care resource utilization related to continuous peripheral nerve blocks in upper extremity surgery may approach 38%. Hamilton et al, 27 however, did not find increased ED resource utilization among 2207 patients undergoing elective shoulder surgery with and without blocks at their institution, a finding corroborated by their subsequent population study of 59 644 Ontario residents. 4 Liu et al reported that among 103 476 patients undergoing outpatient arthroscopic surgery at 243 facilities in New York state, the most common reason for an unanticipated acute care encounter within 7 postoperative days (ie, inpatient or ED encounter) is musculoskeletal pain (23.8% of the 1867 acute care patient encounters).…”
Section: Discussionmentioning
confidence: 79%
“…Finally, 28 studies including 27,581 patients were identified as potentially relevant and were selected for the systematic review. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 All of the included studies were published in English. These studies covered the period from January 2000 to May 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of the included studies ranged from 20 to 14,713 adults who underwent various medical procedures under general and local or regional anesthesia in an outpatient setting. General anesthesia was compared to local anesthesia in 15 studies, 10 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 27 , 30 , 33 to spinal anesthesia in 7 studies, 12 , 15 , 25 , 31 , 32 , 34 , 35 and to both in 5 studies. 26 , 28 , 29 , 36 , 37 Medical procedures were different and included laryngoplasty, knee arthroscopy, biopsy, hernia repair, hysteroscopy, and others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations